Sustainable behavior in nature tourism travel: the influence of local infrastructure - Cândido, Luis Felipe; Araújo, Dhieciane de Sousa; Leocádio, Áurio Lúcio; Guimarães, Daniel Barboza; Ponchio, Mateus Canniatti (Revista de Administração da UFSM, 2024)
Purpose: To analyze the influence of local tourism infrastructure on sustainable behavior. Methodology: A survey was conducted with 209 tourists visiting five cities located in the northeast region of Brazil, encompassing different types of nature tourism such as climbing mountains, taking sunbath, and going to the beach. Through Exploratory Factor Analysis, the collected data were analyzed to reduce the number of variables and group them into factors. Subsequently, a multiple linear regression analysis was performed to assess the influence of constructs related to local infrastructure on sustainable behavior in nature tourism travel. Findings: The results indicate that the sociocultural and ecological dimensions of local infrastructure positively influence the behavior of tourists on nature trips, while public policies’ dimension was not appropriately captured in the study. Practical implications: The research findings can be useful for public managers to improve tourism infrastructure more effectively, induce tourists towards sustainable behavior, and thus achieve sustainable tourism. Originality/value: The study expanded the understanding of sustainable behavior in travel by revealing the dimensions of local infrastructure that positively influence it. It also highlighted the importance of educational actions that promote a local culture of sustainability.